Systematic Literature Review (SLR) on the Effect of Animation Skill Competence on Employability - Mardi; Sutiadiningsih, Any; B, I Gusti Putu Asto; Wrahatnolo, Tri; Anifah, Lilik (Proceeding of International Joint Conference on UNESA, 2024)
In the world of the creative industry, animation had become one of the important things needed to produce interesting visual content. Good animation skills can increase individual competitiveness in the world of work and can also affect the chance of getting a job . This study used the SLR method to collect and analyze recent research on the influence of animation skill competency on employability. In this study, we found that individuals with good animation skills have a better chance of getting a job and can also earn a higher salary. In addition, our research showed that the competency level of animation skills was very important for increasing employability. Individuals with better animation skills tend to have the ability to produce better and more engaging content, thereby adding value to the organization. However, this study also found that other factors such as work experience and education also have a significant effect on employability. Therefore, further research was needed to study the relationship between animation skills and other factors that can affect employability. Improving the competence of animation skills can increase individual employability in the creative industries. This research can provide guidance for individuals and organizations in developing better animation skills to increase competitiveness and employment opportunities